Die trinitariese formule van Matteus 28:19: Fremdkörper of gepaste afsluiting vir die Matteusevangelie? - Hermias C. van Zyl (Verbum et Ecclesia, 2022)
The trinitarian formula of Matthew 28:19: Fremdkörper or an appropriate conclusion? The aim of the article is to investigate whether the trinitarian formula of Matthew 28:19 (‘… baptise them in the name of the Father and of the Son and of the Holy Spirit …’) is a Fremdkörper (foreign body) in the Gospel of Matthew or a meaningful ending to the Gospel. To achieve this, the following aspects were investigated: The tradition history of the formula; Matthew 28:16–20 forming the immediate context of the formula; and the trinitarian notion within the wider context of Matthew’s Gospel. The latter aspect required the following texts to be examined: The heavenly genealogy of Jesus (1:1–25); the baptism of Jesus (3:13–17); the transfer of power to the Son in 11:27; and the trinitarian baptismal formula of 28:19 becoming a ‘replacement’ for the baptismal activity of John the Baptist in Matthew. The conclusion of the study is that the trinitarian formula of 28:19 is not an afterthought to the Gospel but was carefully prepared by Matthew in his Gospel narrative. It thus forms one of the ‘logical highpoints’ of the Gospel that inaugurated the discipling of the nations.